Decolonizing Sociological Knowledge: A Bibliometric Exploration of Postcolonial and Global South Contributions (2014–2024) - Ismail, Ismail; Linda Safitra; Fransiskus Novrianto Pakpahan; Rifai Rifai (Tinta Emas Institute, 2025)
The decolonization of sociological knowledge is critically important for challenging enduring Eurocentric dominance and epistemic inequalities in the discipline, yet empirical assessments of Global South contributions remain scarce. This study addresses this gap by conducting a bibliometric analysis (2014–2024) of 496 Scopus-indexed documents to examine the visibility and integration of postcolonial and Global South scholarship in sociology. Using VOSviewer for co-citation and bibliographic coupling analyses, the study reveals persistent marginalization: fewer than 15% of citations in high-impact journals reference works from Asia, Africa, or Latin America, while 62% of decolonization-related publications originate from the U.S. and Canada. Key findings highlight the hegemony of Western theoretical canons (e.g., Bourdieu, Foucault) and the exclusion of Southern epistemologies (e.g., Ubuntu, Buen Vivir), exacerbated by metric systems privileging Scopus/WoS-indexed journals. The results underscore the need for structural interventions—curricular reforms, inclusive citation practices, and alternative databases—to democratize knowledge production. This research contributes empirical evidence to decolonial debates, offering pathways to transform sociology into a pluralistic discipline that centers marginalized voices and addresses global epistemic injustices.